Ответ:
........................
Объяснение:
1)(x)^2 + 2*x*10 +(10)^2= x^2+20x +100.
2)(6)^2-2*6*a+(a)^2= 36-12a+a^2.
3)(6-a)(6+a)^2= (6-a)*(6)^2+2*6*a+(a)^2=(6-a)*36+12a+a^2.
4)x^2-25
5)(2a-3)^2= (2a)^2- 2*2a*3+(3)^2= 4a^2 -12a+9.
6) 4a^2-9
7)(3x)^2+2*3x*4y+(4y)^2= 9x^2+24xy+16y^2.
8)(12)^2-2*12*2b+(2b)^2= 144-48b+4b^2.
9)81-c^2.
10)(31)^2 + 2*31*z+(z)^2=62+62z+z^2.
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
........................
Объяснение:
Объяснение:
1)(x)^2 + 2*x*10 +(10)^2= x^2+20x +100.
2)(6)^2-2*6*a+(a)^2= 36-12a+a^2.
3)(6-a)(6+a)^2= (6-a)*(6)^2+2*6*a+(a)^2=(6-a)*36+12a+a^2.
4)x^2-25
5)(2a-3)^2= (2a)^2- 2*2a*3+(3)^2= 4a^2 -12a+9.
6) 4a^2-9
7)(3x)^2+2*3x*4y+(4y)^2= 9x^2+24xy+16y^2.
8)(12)^2-2*12*2b+(2b)^2= 144-48b+4b^2.
9)81-c^2.
10)(31)^2 + 2*31*z+(z)^2=62+62z+z^2.